2006
DOI: 10.1038/modpathol.3800633
|View full text |Cite
|
Sign up to set email alerts
|

Transformation-specific matrix metalloproteinases, MMP-7 and MMP-13, are present in epithelial cells of keratoacanthomas

Abstract: Keratoacanthomas are rapidly growing hyperproliferative skin tumors that may clinically or histologically be difficult to distinguish from well-differentiated squamous cell cancers (SCCs). UV light, trauma, and immune suppression represent their etiological factors. As matrix metalloproteinases (MMPs) are implicated at all stages of tumorigenesis, we investigated the expression profile of several cancer-related MMPs to find markers that would differentiate keratoacanthomas from SCCs and shed light to the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…The finding of MMP-7 expression associated with mitoses agrees with findings in cell culture [3]. Previous studies have shown the transformation specific nature of MMP-7 [23,30], but our current data do not support the idea that this MMP would be upregulated by immunosuppression. The other matrilysin now studied for the first time in a large set of BCCs, MMP-26, was only rarely seen in the BCC epithelium or stromal cells, suggesting that it is not essential for the growth or angiogenesis in BCCs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The finding of MMP-7 expression associated with mitoses agrees with findings in cell culture [3]. Previous studies have shown the transformation specific nature of MMP-7 [23,30], but our current data do not support the idea that this MMP would be upregulated by immunosuppression. The other matrilysin now studied for the first time in a large set of BCCs, MMP-26, was only rarely seen in the BCC epithelium or stromal cells, suggesting that it is not essential for the growth or angiogenesis in BCCs.…”
Section: Discussionsupporting
confidence: 85%
“…Sections were pretreated with 10 mg/ml trypsin or incubation in citrate buffer in a +95°C water bath. We used mostly mouse monoclonal antibodies to study the localization of MMP-1 [24], TIMP-1 (1:100, IM63L, Calbiochem), and TIMP-3 (1:400, IM43L, Calbiochem) as previously described [23,30]. Diaminobenzidine (DAB) or aminoethylcarbazole (AEC) were used as chromogenic substrates and Mayer hematoxylin as counterstain.…”
Section: Methodsmentioning
confidence: 99%
“…Some KA cases that were initially diagnosed as benign progressed to be metastatic, exhibiting aggressive behavior (3)(4)(5). The immunohistochemical markers that have been used for years to distinguish between SCC and KA in studies are: p53, proliferating cell nuclear antigen , telomerase and COX-2 , transforming growth factor-α, angiotensin-type I receptor, vascular cell adhesion molecule, intercellular adhesion molecule, Ki-67, p16 tumor suppressor antigen, matrix metalloproteinases, syndecan-1 and Bcl-2 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, none of these studies have been able to provide reliable and specific criteria with which to distinguish between these two tumors.…”
mentioning
confidence: 99%
“…Advantages in distinguishing the two diagnoses would bring about fewer unnecessary surgeries, lower burden on the healthcare system and most importantly less anxiety for the patients. Over the years, elaborate work of investigating possible biomarkers for the distinction of KA from SCC has been performed, including studies of p53,8 proliferating cell nuclear antigen,9 angiotensin type I receptor,10 vascular cell adhesion molecule, intracellular adhesion molecule,11 telomerase, cyclo‐oxygenase‐2,12 KI‐67,13 p16 tumour suppressor antigen,14 matrix metalloproteinases,15 syndecan‐116 and Bcl‐2 17. Still, none of these studies have provided specific or reliable distinguishing criteria.…”
Section: Overview Of the Investigated Antigensmentioning
confidence: 99%